Mobile Application Based on Geolocation and Voice Assistant for the Management of Donations in the NGO Mi Canto, Cajamarca - Cahuana Calua, Jhoan Manuel; Suarez Guevara, Sleyter Alejandro; Sierra-Liñan, Fernando (LACCEI, 2025)
Currently, non-profit organizations in regions such as Cajamarca face serious limitations to efficiently manage food, clothing and toy donations. This technological gap increases response times, raises operating costs and reduces the capacity to serve people in vulnerable situations. Leveraging the potential of mobile applications, this study contributes to informatics by demonstrating how the use of agile technologies and cloud storage can optimize logistics processes in social environments. The methodology of this research was applied quantitative approach, pre-experimental design, explanatory scope and non-probabilistic convenience sampling using a sample of 28 participants. The development was carried out in Android Studio using Java, Firebase, Flutter and Visual Studio Code, guided by the Mobile-D agile methodology. The results after the implementation of the application showed a 50.72% reduction in management time, a 78.33% reduction in costs and a 91.74% increase in the number of donations. Likewise, user satisfaction reached very high levels in all the evaluated dimensions of the post. Validation by expert judgment also confirmed the clarity, relevance and consistency of the instrument. These results highlight the effectiveness of the mobile solution developed to optimize internal processes, foster a culture of solidarity and improve interaction between users and social organizations.